Analysis of Liquid Xenon Tank Filling Process in Different Gravity Environments - Zong-Yu Wu; Chao Jiang; Yong Chen; Kai Li; Yiyong Huang; Yun Cheng (Aerospace, 2025)
With the advancement in deep-space exploration, the injection technology using xenon as a working fluid in electric propulsion systems has emerged as a key area of interest. To delve into the gas-liquid dynamics of the liquid xenon injection process and the influence of gravity on this mechanism, this investigation employs a VOF two-phase flow model coupled with the Lee model to elucidate the characteristics of the two-phase flow during microgravity conditions. The findings uncover that in the absence of gravitational forces, gas-liquid stratification does not occur during the filling process. Consequently, this leads to an even distribution of gas and liquid within the tank, which in turn prolongs the filling duration in orbiting scenarios.